Simultaneous transmission of adenocarcinoma after kidney transplantation. Report of two rare cases - Exman, Pedro; Meireles, Sibele Inacio; Couldry, Renata; Neto, Elias David; Sabbaga, Jorge (Brazilian Journal of Oncology, 2017)
Malignancy related to donor after transplantation is a very rare situation that can be classified in two categories. The first is donor cell derived malignancy and the second, most rare, is tumor transmission which include the development of malignancy in a misdiagnosed donor pre-existent solid organ. This condition has good prognosis mainly because of recipient immune response, and patients are treated with explatantion of the graft associated with immunotherapy withdraw. Accordingly, we report two cases of female patients that have received their kidneys and tumors transplanted from the same male donor which DNA analysis confirm the same donor origin. Both patients were treated with the same therapy but different disease presentation.
Keywords: Adenocarcinoma; Transplantation; Transmission; Neoplasms/immunology